2017
DOI: 10.1002/cctc.201700089
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of d‐Glucose to Glucaric Acid Using Au/C Catalysts

Abstract: The reactivity of Au and AuBi nanoparticles supported on activated carbon AC was investigated in the direct oxidation of glucose to glucaric acid. The catalysts were very active, regardless of the Au nanoparticles size, but the catalyst with the smallest average particle diameter was the least selective to glucaric acid because of the enhanced consecutive oxidative degradation of the intermediately formed gluconic acid. The reaction network included the fast oxidation of glucose to gluconic acid, which was the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 60 publications
3
77
0
Order By: Relevance
“…Indeed, at 70 • C and after 4 h of reaction in the presence of K 2 CO 3 , a noncatalyzed (thermal) oxidative degradation of glucose was observed. Similar results already described in the literature [28][29][30] confirmed the formation of formic, acetic, and propionic acids, as well as of 24 hydrocarboxylic acids and 12 corresponding lactones. The aldehyde and alcohol functions of monosaccharides (such as glucose) can be oxidized giving high added-value compounds (see Scheme 1).…”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…Indeed, at 70 • C and after 4 h of reaction in the presence of K 2 CO 3 , a noncatalyzed (thermal) oxidative degradation of glucose was observed. Similar results already described in the literature [28][29][30] confirmed the formation of formic, acetic, and propionic acids, as well as of 24 hydrocarboxylic acids and 12 corresponding lactones. The aldehyde and alcohol functions of monosaccharides (such as glucose) can be oxidized giving high added-value compounds (see Scheme 1).…”
Section: Introductionsupporting
confidence: 89%
“…Studies confirmed that the best catalytic activity and the highest TOF were observed with a mass ratio of 70/20/10 [48]. Recently, Hutchings's group [28] studied several Au bimetallic catalysts for the oxidation of glucose and cellobiose. They found that the preparation method plays a crucial role in the catalytic activity of supported Au catalysts especially in the case of base-free oxidation processes.…”
Section: Multimetallic Au-based Catalystsmentioning
confidence: 86%
See 1 more Smart Citation
“…In recent decades, supported gold nanoparticles have been extensively studied because of their unusual catalytic properties [1][2][3][4]. It is well recognized that the size of gold nanoparticles determines both the activity and the selectivity of the final catalyst [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…It is well recognized that the size of gold nanoparticles determines both the activity and the selectivity of the final catalyst [4,5]. It is also considered that the drastic change of the catalytic properties of nanoparticles is due to their new properties (physical and chemical) which are created when their size decreases, mainly due to the significant increase in the number of atoms on the surface [5][6][7].…”
Section: Introductionmentioning
confidence: 99%